Implementasi Media Pembelajaran Quizizz sebagai Penilaian Harian Teks Persuasi pada Peserta Didik Kelas VIII SMP Negeri 1 Pecangaan - Rifana Yuniartanti; Asep Purwo Yudi Utomo; Neni Widyawati; Rochimmatussaadah Rochimmatussaadah; Fahrizal Lalang Sitoro (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Along with the development of science and technology is very influential in one's life. In the world of education, learning technology has a positive impact, including students being given the flexibility to access information sources from social media. In addition, along with the development of technology that is happening as it is today. Educators are expected to be able to provide fun learning by providing learning media that suit the needs of students, educators can also utilize applications such as power point, YouTube, or other e-learning as learning media. The goal is to create a fun interactive learning atmosphere, using Quizizz can also increase interest and motivation in learning and make it easier for educators to give quizzes or material to students. This study uses descriptive qualitative research methods, related to data collection, researchers use several techniques such as observation, interviews, and documentation. The results obtained by students are also mostly above the KKM, so this Quizizz learning media is very suitable to be used as practice questions which are carried out not only in face-to-face learning, but online learning can also be done. Because, with the unlimited space and time given which requires that work be done at that time it also makes it very flexible and efficient because it does not require paper and writing instruments so that the collection is in accordance with the needs and agreements that have been made between students and educators.